Participatory storyworld building for unlocking climate adaptation - Benjamin T. Pederick; Martin Potter; Hailey Cooperrider; Sidney Icarus; Donna Luckman; Rebecca Dahl; Mark Elliot; Trish Cave; Jason Tampake; Brett A. Bryan (Global Environmental Change, 2025)

FishSounds Versions 2 and 3: Achieving the Largest Global Database of Fish Sound Production - Audrey Looby; Sarah Vela; Aaron N. Rice; Santiago Bravo; Hailey L. Davies; Kelsie A. Murchy; Rodney Rountree; Laura K. Reynolds; Charles W. Martin; Francis Juanes; Kieran D. Cox (Global Ecology and Biogeography, 2025)
Motivation Fish sounds are integral to a variety of ecological functions, including reproduction, predator–prey interactions and recruitment, with ever‐growing interest in their relationships to anthropogenic impacts and applications for passive acoustic monitoring. Until recently, however, fish sound production data were often not easily accessible, limiting research, management and public awareness. FishSounds.net launched in 2021 to compile and disseminate global fish sound production information and recordings. Here, we describe the subsequent FishSounds version releases 2.0, 2.1, 2.2, 3.0 and 3.1 (cumulatively referred to as Versions 2 and 3). We updated the core dataset to include any fish species studied for sound production up until the year 2023. We added over 1000 new fish sound recordings, collated from FishSounds contributors or Cornell University's Macaulay Library. Connections with FishBase and the World Register of Marine Species were strengthened to improve the species information provided on FishSounds and facilitate data sharing. We also created several interactive visualisation tools, including a dendrogram and map view, to allow users to explore trends in known fish sound production. These updates have made FishSounds now the largest catalogue of fish sound production knowledge, utilised by over 17,000 users annually and featuring 1252 fish species studied across 1013 references as well as 1304 recordings. Main Types of Variables Contained Fish sound production information compiled from the scientific literature, representative fish sound recordings with associated metadata and supporting images and species data drawn from other repositories. Spatial Location and Grain Global. Time Period and Grain 1874–2023. Major Taxa and Level of Measurement Fishes (Agnatha, Chondrichthyes, Sarcopterygii, Actinopterygii). All sound production information and most recordings have species‐level identification, with any others identified to the lowest possible taxonomic level. Software Format The complete database is presented on FishSounds.net , with versioned image, audio, tabular and text files in a Borealis data repository.

High‐resolution analysis of sediments from Eighteen Mile Swamp (eastern Australia) records its transition from a fluctuating coastal lagoon to stable freshwater swamp - Jonathan C. Marshall; John Tibby; Patrick Moss; Hailey Martin; Allen Gontz; Annie Lau; Geraldine E. Jacobsen; Haidee Cadd; Patricia S. Gadd; Peter Negus; GLENN B. Mcgregor; Harald Hofmann; et al. (Journal of Quaternary Science, 2025)
This research documents the paleoenvironmental evolution of Eighteen Mile Swamp on North Stradbroke Island (Minjerribah), Australia, from oscillating coastal lagoon into stable freshwater swamp over the last ca. 1600 years. We analyzed multiple sediment cores via physical description, acid sulfate soil assays, particle size analysis, diatom and pollen assemblages, photosynthetic pigment content, and Itrax XRF spectrometry, alongside ground‐penetrating radar cross‐sections. This provided a detailed ecological, geochemical and chronological framework, derived from radiocarbon, Pu and 210 Pb dating, for the wetland's evolution. Results indicate spatial complexity in the timing of a pronounced shift in sedimentary conditions between ca. 300 and 1000 years ago, from estuarine mud to freshwater peat, marked by abrupt chemical and ecological changes. Unexpectedly, there were at least three and potentially many periods of dominant freshwater influence within the primarily estuarine phase, suggesting episodic estuarine closure and freshening by groundwater influx. Results provide critical insights into the complex response of subtropical wetland systems to environmental change, emphasizing the importance of interdisciplinary approaches in understanding both sedimentologic and geomorphic responses in coastal wetlands, and their potential vulnerability to future climate change. The study of Eighteen Mile Swamp is significant as it provides a detailed paleoenvironmental reconstruction that documents the wetland's evolving nature over the past two millennia. This research highlights the importance of understanding historical responses of wetlands to environmental changes, which helps inform their current and future management, conservation and restoration efforts, particularly in the context of climate change and human impacts. This study also serves as a tribute to the late Lynda Petherick, acknowledging her contributions in this field.

Performance of three techniques for diagnosing equine tapeworm infection - Hailey C. Anderson; Shaelin F. Mitchell; Nichol E. Ripley; Martin K. Nielsen (Veterinary Parasitology, 2024)

Intestinal nerve cell injury occurs prior to insulin resistance in female mice ingesting a high-fat diet - Yvonne Nyavor; Rachel Estill; Hannah Edwards; Hailey Ogden; Kaila Heideman; Kiefer Starks; Christopher Miller; George May; Lance Flesch; John McMillan; Martin Gericke; Larry Forney; et al. (Cell and Tissue Research, 2019)